2007
DOI: 10.1242/dev.003814
|View full text |Cite
|
Sign up to set email alerts
|

Hand2is necessary for terminal differentiation of enteric neurons from crest-derived precursors but not for their migration into the gut or for formation of glia

Abstract: Hand genes encode basic helix-loop-helix transcription factors that are expressed in the developing gut, where their function is unknown. We now report that enteric Hand2 expression is limited to crest-derived cells, whereas Hand1 expression is restricted to muscle and interstitial cells of Cajal. Hand2 is developmentally regulated and is intranuclear in precursors but cytoplasmic in neurons. Neurons develop in explants from wild-type but not Hand2 -/-bowel, although, in both, crest-derived cells are present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 66 publications
0
73
0
Order By: Relevance
“…We observed a similar, but more complete, coincidence of Sox10 and Phox2b in the pancreas, possibly reflecting a more synchronous arrival and differentiation of neural crest cells in the pancreas. As in the gut (D'Autreaux et al, 2007), markers of differentiated neurons and glia then appeared shortly thereafter, along with lineage-specific markers, such as the bHLH transcription factor Hand2 (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…We observed a similar, but more complete, coincidence of Sox10 and Phox2b in the pancreas, possibly reflecting a more synchronous arrival and differentiation of neural crest cells in the pancreas. As in the gut (D'Autreaux et al, 2007), markers of differentiated neurons and glia then appeared shortly thereafter, along with lineage-specific markers, such as the bHLH transcription factor Hand2 (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Conditional ablation of Hand2 in NCCs has revealed a crucial role for Hand2 in the development of sympathetic ganglion neurons (Hendershot et al, 2008;Morikawa et al, 2007), the enteric nervous system (Hendershot et al, 2007;D'Autreaux et al, 2007) and the cardiac outflow tract (Holler et al, 2010). In addition, conditional inactivation of Hand2 in the developing palatal epithelium has uncovered a role for Hand2 in palatal shelf fusion (Xiong et al, 2009).…”
Section: Ba/bamentioning
confidence: 99%
“…Previous studies have identified molecules that can affect the differentiation of enteric neural crest-derived cells into enteric neurons (Blaugrund et al, 1996;Chalazonitis et al, 2004Chalazonitis et al, , 2008D'Autreaux et al, 2007;Okamura and Saga, 2008). For example, the disruption of the Notch signalling pathway has recently been shown to result in premature neurogenesis and a decrease in gliogenesis (Okamura and Saga, 2008).…”
Section: Cgrpmentioning
confidence: 99%
“…A similar result was obtained in mice that lack the transcription factor, Hand2 (D' Autreaux et al, 2007). In Hand2 knockout mice, enteric neurons fail to develop, however the de- velopmental appearance and density of enteric glial cells was not affected (D'Autreaux et al, 2007). Endothelin-3 inhibits the neuronal differentiation of enteric neural crestderived cells in vitro Wu et al, 1999), and mice lacking endothin-3 have delayed migration of crest-derived cells along the developing gut (Kapur et al, 1992(Kapur et al, , 1993Barlow et al, 2003).…”
Section: Cgrpmentioning
confidence: 99%
See 1 more Smart Citation